2004
DOI: 10.1056/nejmoa040566
|View full text |Cite
|
Sign up to set email alerts
|

Public-Access Defibrillation and Survival after Out-of-Hospital Cardiac Arrest

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
135
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 961 publications
(141 citation statements)
references
References 19 publications
1
135
0
3
Order By: Relevance
“…A cluster randomized controlled study showed that PAD deployment and training of lay volunteers in CPR and AED use significantly increased survival to discharge rates in comparison with volunteer CPR training only (23.4% vs 14.0%; relative risk=2.0) (Table 2). 7 A meta‐analysis of three studies (one assessing PAD use by lay volunteers7 and two assessing PAD use by fire fighters and police officers19, 20) assessed the effects of PAD use with CPR by nonhealthcare professionals and showed a significantly favorable association with survival to discharge compared with CPR alone (relative risk=1.39) 6. In contrast, home placement of PADs is not a promising strategy.…”
Section: Pad Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cluster randomized controlled study showed that PAD deployment and training of lay volunteers in CPR and AED use significantly increased survival to discharge rates in comparison with volunteer CPR training only (23.4% vs 14.0%; relative risk=2.0) (Table 2). 7 A meta‐analysis of three studies (one assessing PAD use by lay volunteers7 and two assessing PAD use by fire fighters and police officers19, 20) assessed the effects of PAD use with CPR by nonhealthcare professionals and showed a significantly favorable association with survival to discharge compared with CPR alone (relative risk=1.39) 6. In contrast, home placement of PADs is not a promising strategy.…”
Section: Pad Programsmentioning
confidence: 99%
“…When arrest is suspected, dispatchers may instruct PAD use if available by emphasizing the diagnostic function, which can attenuate difficulties in identifying cardiac arrest 18. However, if facilitating PAD use by untrained lay people does not work, an additional planned response strategy may be considered in Japan, whereby volunteers are systematically trained 7. Further studies are needed to find effective measures to facilitate bystander CPR using PADs and to improve the accuracy of dispatcher recognition and instructions.…”
Section: Issues Concerning Pad That Needs To Be Addressedmentioning
confidence: 99%
See 1 more Smart Citation
“…Long‐term survival can increase as much as 2 to 3 times if a bystander/first responder also uses an automated external defibrillator (AED) before emergency medical service (EMS) arrival 2, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16. Many studies, including a prospective, randomized trial, have shown that public access defibrillation (PAD) programs improve the rate of survival among patients with an OHCA.…”
Section: Introductionmentioning
confidence: 99%
“…Early defibrillation improves the survival of victims of sudden cardiac arrest 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16. However, it is often difficult to shorten the time from the cardiac arrest to the defibrillation utilizing the emergency medical service.…”
Section: Introductionmentioning
confidence: 99%